A little bit of sex matters for genome evolution in asexual plants - Hojsgaard, Diego; Hörandl, Elvira (Frontiers in Plant Science, 2015)
Genome evolution in asexual organisms is theoretically expected to be shaped by various factors:first, hybrid origin and polyploidy confer a genomic constitution of highly heterozygous genotypes with multiple copies of genes;second, asexuality confers a lack of recombination and variation in populations, which reduces the efficiency of selection against deleterious mutations;hence, the accumulation of mutations and a gradual increase in mutational load (Muller’s ratchet)would lead to rapid extinction of asexual lineages;third, allelic sequence divergence is expected to result in rapid divergence of lineages (Meselson effect).Recent transcriptome studies on the asexual polyploid complex Ranunculus auricomus using single-nucleotide polymorphisms confirmed neutral allelic sequence divergence within a short time frame, but rejected a hypothesis of a genome-wide accumulation of mutations in asexuals compared to sexuals, except for a few genes related to reproductive development.We discuss a general model that the observed incidence of facultative sexuality in plants may unmask deleterious mutations with partial dominance and expose them efficiently to purging selection.A little bit of sex may help to avoid genomic decay and extinction.